The clinical and dermoscopic features of invasive cutaneous squamous cell carcinoma depend on the histopathological grade of differentiation. (9th March 2015) - Lallas, A.; Pyne, J.; Kyrgidis, A.; Andreani, S.; Argenziano, G.; Cavaller, A.; Giacomel, J.; Longo, C.; Malvestiti, A.; Moscarella, E.; Piana, S.; Specchio, F.; et al.
Summary Background Little is known about the variability of the dermoscopic criteria of squamous cell carcinoma (SCC) according to the histopathological differentiation grade. Objectives To evaluate whether specific dermoscopic criteria can predict the diagnosis of poorly differentiated SCC compared with well‐ and moderately differentiated SCC. Methods Clinical and dermoscopic images of SCCs were retrospectively evaluated for the presence of predefined criteria. Univariate and adjusted odds ratios were calculated. Discriminant functions were used to plot receiver–operator characteristic curves. Results Of 143 SCCs included, 48 (33·5%) were well differentiated, 45 (31·5%) were moderately differentiated and 50 (35·0%) were poorly differentiated. Flat tumours had a fourfold increased probability of being poorly differentiated. Dermoscopically, the presence of a predominantly red colour posed a 13‐fold possibility of poor differentiation, whereas a predominantly white and white–yellow colour decreased the odds of poorly differentiated SCC by 97% each. The presence of vessels in more than 50% of the tumour's surface, a diffuse distribution of vessels and bleeding were significantly associated with poor differentiation, while scale/keratin was a potent predictor of well‐ or moderately differentiated tumours. Conclusions Dermoscopy may be regarded as a reliable preoperative tool to distinguish poorly from well‐ and moderately differentiated SCC. Given that poor differentiation of SCC represents an independent risk factor for recurrence, metastasis and disease‐specific death, identifying poorly differentiated tumours in vivo may enhance their appropriate management.